Modes of photography: Cultural and Socioeconomic Transformations (Research, Society and Development, 2019)
In a globalized world, intensified with the advent of digital information and communication technologies, new habits and practices are experienced by society. All segments have undergone processes of innovation and adaptation, in order to live and survive in new conditions. This article presents research results that investigated culture “makers” of the handicrafts, antiques, fashion and visual arts segments. We seek an analysis embedded in contemporary conceptual supports of sociability in urban contexts, linked to perceptions of time, space and connection, flowing into the city through the communication flows in a context of globalization and digitalization. Here we present one of the characters investigated, a photographer, representative of the visual arts. The research showed that it is possible for the “makers” to live from their knowledge, from their way of doing, mainly, by taking advantage of the facilities of new technologies, as well as an intangible, inexhaustible, symbolic input: creativity.